Effects of igneous intrusions on diagenesis and reservoir quality of sandstone in the Songliao Basin, China. (May 2021) - Rong, Hui; Jiao, Yangquan; Wu, Liqun; Zhao, Xinfu; Cao, Minqiang; Liu, Weihong
Abstract: An exceptional example for evaluating effects of igneous intrusions on diagenesis and reservoir quality of sandstone has been found in the Qianjiadian area, Songliao Basin. Sandstone of the Upper Crataceous Yaojia Formation near diabase dikes is characterized by kaolinite, illite-smectit mixed-layer minerals, ankerite, scheelite, sphalerite, galena, chalcopyrite, brannerite, and dissolution of quartz, alkali feldspar, plagioclase and siderite. Diagenesis related to the intrusion of diabase dikes has gone through two stages. The early stage with a temperature and salinity of 175–225 °C and 12.0–18.0 wt% NaCl equiv respectively is featured by kaolinite and dissolution of quartz, alkali feldspar, plagioclase and siderite, whereas the late stage with a temperature and salinity of 125–150 °C and 8.0–10.0 wt% NaCl equiv respectively is distinguished by ankerite, scheelite, sphalerite, galena, chalcopyrite, brannerite and dissolution of quartz. Values of the plane porosity, pore diameter, porosity and permeability covary with the distance between sandstone and dike contacts: the values rapidly decrease when the distance decreases while the values gradually increase when the distance increases. Correspondingly, the extent to which the reservoir quality was reduced is far smaller than that to which the reservoir quality was improved. Two-stage hydrothermal fluids have been aroused by the diabase dikes: acidic in early stage and alkalic in late stage, and affecting range of the former is wider than that of the later. These hydrothermal fluids lead to development of secondary pores in the sandstone. Highlights: Mineralogical signs of sandstone reformed by intrusions were established. Porosity are decreasing closer to dikes and increasing further away from dikes. Hydrothermal fluids aroused by dikes result in formation of secondary pores.